Strain Pattern on Electrocardiogram Is Associated with Increased Carotid Intima-Media Thickness in Patients with Aortic Valve Stenosis - Roscani, Meliza Goi; Augusto, Gustavo N. [UNESP]; Valadão, Tainá F.C. [UNESP]; Araújo, Jonas A. [UNESP]; Duarte, Juliana C. [UNESP]; Gobbi, Juliana I.F. [UNESP]; Silveira, Liciana V.A. [UNESP]; Coneglian, Regina C. [UNESP]; Rossi, Daniele A. [UNESP]; Zanati, Silméia G. [UNESP]; Matsubara, Beatriz B. [UNESP]; Hueb, João C. [UNESP] (Elsevier, 2016)
Background Coronary artery disease is present in at least 30% of patients with degenerative aortic stenosis (AS). Atherosclerosis also performs an important role in the progression of AS, because of the similarities of pathological mechanisms in both conditions. The electrocardiogram (EKG) strain pattern is associated with structural myocardial change and subendocardial ischemia and has been worldwide used as a marker of AS severity. We hypothesized that EKG strain pattern would be a marker of atherosclerosis as well in AS patients. The aim of this study was to associate the presence of EKG strain pattern in AS patients with the carotid intima-media thickness (CIMT). Methods Fifty-two consecutive patients referred from the cardiology clinic with moderate or severe AS were included in the study and underwent clinical evaluation, EKG, transthoracic echocardiography, and carotid ultrasonography, following statistical analysis of the results. Results There was a significant association between left ventricular EKG strain and increased CIMT (P = 0.001). The presence of strain increased the odds of abnormal CIMT (P = 0.004, odds ratio 9.7, 95% confidence interval 2.4–45.0), in a model adjusted for age and clinical diagnosis of systemic arterial hypertension. Additionally, EKG strain was associated with the presence of atherosclerotic plaque in at least one carotid artery (P = 0.011). Conclusion Our results suggest that AS patients with EKG strain pattern should be further investigated for the diagnosis of subclinical atherosclerotic disease.